Statistical time energy based damage detection in steel plates using artificial neural networks - Paulraj, Murugesa Pandiyan, Prof. Madya; Mohd Shukri, Abdul Majid; Sazali, Yaacob, Prof. Dr.; Mohd Hafiz, Fazalul Rahiman; Krishnan, R. P. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/